Figurines in context. (February 2020) - Frankel, David
Abstract : For 50 years, Peter Ucko's Anthropomorphic figurines (1968) has served as an entry-point for anyone approaching the study of figurines: this new Oxford handbook now provides a broader alternative, which conveniently summarises much current evidence and thinking. Following the standard format of this series, Tim Insoll has brought together a wide array of studies covering many different periods and places as well as diverse approaches to analysis.